Legal mechanisms for protecting persons who have suffered damage and destruction of property as a result of armed aggression against Ukraine - Trufanova , Yuliia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2026)
The article aims to identify the specifics of legal protection for victims of damage and destruction of property as a result of armed aggression against Ukraine by analyzing the relevant legislation. The relevance of the problem of protecting property rights in wartime is substantiated, the main legislative provisions are analyzed, and those that regulate the legal mechanism for protecting property rights during martial law are identified. Key regulatory and legislative acts governing this issue, as well as international legal norms, are analyzed; the peculiarities of legal regulation of property rights are considered, and mechanisms for its protection and defense in conditions of martial law are examined.The existing restrictions on property rights that may be applied in accordance with current legislation are examined, as well as the methods of restoring and protecting violated property rights and the peculiarities of compensating individuals for losses resulting from military aggression. The purpose of the article is to analyze the legal means of regulating compensation for damage caused by aggression against Ukraine, taking into account modern approaches to the protection of the rights of individuals. As a result of the study, it was established that there is a need to reform the national legislation of Ukraine in order to improve the effectiveness of legal regulation of damage compensation procedures and improve the regulatory framework. The most desirable compensation mechanism for Ukraine is the payment of reparations by the aggressor state, which should include compensation for both material losses and non-pecuniary (moral) damage. At the same time, at the present stage, the practical implementation of such a mechanism is objectively impossible.